Hacking the streets: ‘smart’ writing in the smart city - Jordan, Spencer (University of Illinois at Chicago Library, 2016)
As cities become more complex and their communities more dispersed, questions such as ‘where is home? and ‘where and how do I belong?’ are increasingly pertinent. If urban space is a system, then it can be challenged through the spatial practice of its citizens. This contestation is examined as a form of hacking, an activity McKenzie Wark defined as the abstraction of new worlds. Drawing on the outcomes of a research project, this paper argues that digitally-enabled creative writing can play a fundamental role within this process, enabling the reappropriation of the smart city by its citizens.